Efficacy of Some Antibiotics used for the Treatment of Diseased Koi (Anabas Testudineus) Fish (Microbes and Health, 2014)
Naturally diseased climbing perch Anabas testudineus was confirmed to be caused by Aeromonas hydrophila bacteria by aeromonas isolation medium (AIM), 0/129 vibriostatic agent and esculin hydrolysis. Such naturally diseased koi fish weretreated with four antibiotics: captor (chlortetracycline hydrochloride BP 45%), renamox 15% -Vet (amoxicillin trihydrate BP), oxy-Dox-F (oxytetracycline 20% and + doxycycline 10%), renaquine 20% -Vet (flumequine) at lower, recommended and higher doses were performed to examine the efficacy of the drugs. Captor was given at doses of 0.8, 1.0 and 1.2 g/3 litres of water separately. Doses of renamox 15% -Vet were given at 0.8, 1.0 and 1.2 g/litre of water. Doses of oxy-Dox-F were 0.8, 1.0 and 1.5 g/Kg body weight and doses of renaquine were 10, 12, and 15 mg/Kg body weight. Among the four antibiotics, effect of captor and renaquine at recommended dose showed the best result where 100% fish were recovered. However, renamox and oxy-Dox-F showed best result at higher dose. DOI: http://dx.doi.org/10.3329/mh.v3i1.19770 Microbes and Health, June 2014. 3(1): 7-8